ONE-STEP SYNTHESIS OF ALKYLTRIMETHYLAMMONIUM-INTERCALATED MAGADIITE - Pastore H.O.; Munsignatti M.; Mascarenhas A.J.S. (My University, 2000)
Cetyltrimethylammonium-and tetradecyltrimethylammonium-intercalated magadiites were prepared by direct syntheses, starting from sodium metasilieate (NaaO/SiO2 = 1.0) and nitric acid. Total substitution of sodium by cetyltrimethylammonium or tetradecyltrimetbylammoniurn cations was not achieved in the range of surfactant : silicon molar ratios used in this study. When a phosphoniun-based surfactant replaces the ammonium surfactants in the same procedure, the result of the synthesis is a mixture of quartz and unmodified surfactant. If dodecylammonium bromide is used, an MCM-41 molec-ular sieve is obtained. The substitution of the silicon source by tetramethylammonium silicate or of nitric acid by hydrochloric, hydrofluoric, or acetic acids also yields MCM-41 molecular sieves, indicating that the formation of magadiite is greatly dependent on the presence of sodium cations and nitrate anions.